Respostas

2014-06-29T19:27:51-03:00
Dadas as Funções 

f(x) = x² + 4x - 5 e g(x) = 2x - 3

Determine as seguintes funções compostas:

A) f(g(x)).
     f(x) = x² + 4x - 5   substituir o (x)
f(2x-3) = (2x-3)² + 4(2x-3) - 5-----------------fazer a distributiva
f(2x-3) = (2x-3)(2x-3) + 8x - 12 - 5
f(2x-3) = 4x² - 6x  - 6x + 9 + 8x - 12 - 5
f(2x-3) = 4x² - 12x + 9 + 8x - 12 - 5 -----------arrumar a casa
f(2x-3) = 4x² -12x + 8x + 9 - 5
f(2x-3) = 4x² - 4x + 4
então

f(g(x)) = 4x² - 4x + 4

B) g(f(x)).
             g(x) = 2x - 3
g(x² + 4x - 5) = 2(x² + 4x - 5) - 3   fazer a distributiva
g(x² + 4x - 5) = 2x²  + 8x -10 - 3
g(x² + 4x - 5) = 2x² + 8x - 13
então

g(f(x)) = 2x² + 8x - 13

1 5 1